Antarctobius bidentatus - Morrone, Juan J. (Zenodo, 2011)
Antarctobius bidentatus (Champion, 1918) Hypera bidentata Champion, 1918a: 176 (type locality: Argentina: Falkland Islands (Islas Malvinas), East Island; type material: H: BMNH). Listroderes (Antarctobius) bidentatus; Kuschel, 1955: 289. Antarctobius bidentatus; Morrone, 1992a: 6. Distribution. Falkland Islands (Islas Malvinas) (Morrone, 1992a; Posadas, 2008). Published as part of Morrone, Juan J., 2011, Annotated checklist of the tribe Listroderini (Coleoptera: Curculionidae: Cyclominae) 3119, pp. 1-68 in Zootaxa 3119 (1) on page 15, DOI:10.11646/zootaxa.3119.1.1, http://zenodo.org/record/5246257